The Prince and The Pauper - "Mark Twain" (,Puffin Classics London, 1994)
The Prince and the Pauper is a novel by Mark Twain that tells the story of two boys who look alike and switch places1234. One is Prince Edward, the son of King Henry VIII, and the other is Tom Canty, a poor Londoner234. The novel explores the themes of class, identity, and justice as the boys experience each other$1 (Bs lives34. The novel ends with Edward regaining his throne and befriending Tom14s
Keywords: Children fiction